Dietary live microbe intake and its association with Parkinson’s disease in American adults: an NHANES analysis (1999–2018) - Zou, He; Zhu, Tao; Chen, Xiaoshu; Lu, Yifei (Frontiers in Nutrition, 2025)
BackgroundDiet plays a crucial role in sustaining a healthy body, and microbes have attracted significant scholarly interest in recent years as an essential component of diet. This study aims to explore the association between dietary live microbe intake and the incidence of Parkinson’s Disease (PD) among adults over 40 years old.MethodsA total of 26,033 subjects in NHANES 1999–2018 were included in this study, comprising 314 patients with PD, which were divided into three groups based on their intake of foods with different levels of microbial content: high, medium, and low. The assessment on subjects’ dietary live microbe intake was conducted through the self-reported questionnaire.ResultsThe distribution of subjects based on dietary live microbe intake was as follows: 34.5% had a low intake, 45.4% had a medium intake, and 20.1% had a high intake. A multivariable logistic regression analysis revealed that subjects with high (OR = 0.52, 95% CI: 0.37–0.74) and medium (OR = 0.73, 95% CI: 0.57–0.93) dietary live microbe intake exhibits a reduced prevalence of PD compared to those with low intake. Restricted cubic spline (RCS) analysis indicated a significant linear association between dietary live microbe intake and the prevalence of PD. Furthermore, stratified analyses demonstrate that the association among research variables was more pronounced in subjects without obesity.ConclusionThis study demonstrates an inverse linear association between dietary live microbe intake and the prevalence of PD.